2021
DOI: 10.1186/s12913-021-06232-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the barriers and facilitators of psychological safety in primary care teams: a qualitative study

Abstract: Background Psychological safety is the concept by which individuals feel comfortable expressing themselves in a work environment, without fear of embarrassment or criticism from others. Psychological safety in healthcare is associated with improved patient safety outcomes, enhanced physician engagement and fostering a creative learning environment. Therefore, it is important to establish the key levers which can act as facilitators or barriers to establishing psychological safety. Existing lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
1
29
0
1
Order By: Relevance
“…As primary care professionals are facing growing pressure, anxiety and uncertainty with increasingly complex population health challenges, a psychologically safe work environment should be guaranteed. However, extant research on psychological safety in health care has dominantly focused on secondary care and provides little information on the impact of psychological safety on quality and patient safety in primary care settings [29]. We found that CHCs with high psychological safety levels had a positive influence on nurse‐reported quality of care.…”
Section: Discussionmentioning
confidence: 74%
“…As primary care professionals are facing growing pressure, anxiety and uncertainty with increasingly complex population health challenges, a psychologically safe work environment should be guaranteed. However, extant research on psychological safety in health care has dominantly focused on secondary care and provides little information on the impact of psychological safety on quality and patient safety in primary care settings [29]. We found that CHCs with high psychological safety levels had a positive influence on nurse‐reported quality of care.…”
Section: Discussionmentioning
confidence: 74%
“…Extensive research has related psychological safety and the absence of anxiety to improved mood [ 85 ]. Psychological safety regulates people’s emotional well-being by motivating a desire for social support to reduce anxiety [ 86 , 87 , 88 ]. When anxiety is reduced, the quality of social relationships improves, enhancing healthspans [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leaders play a vital role in fostering psychological safety. Remtulla et al (2021) emphasized leader attributes such as friendliness, support, and encouraging team member participation as key facilitators. Additionally, leader inclusiveness, as demonstrated in a study of 106 medical residents (Appelbaum et al, 2016), is associated with higher levels of psychological safety.…”
Section: Psychological Safetymentioning
confidence: 99%